2022
DOI: 10.3390/ijerph191711056
|View full text |Cite
|
Sign up to set email alerts
|

How Work-Family Conflict Influenced the Safety Performance of Subway Employees during the Initial COVID-19 Pandemic: Testing a Chained Mediation Model

Abstract: This study examined the impact of work-family conflict on subway employees’ safety performance during the initial wave of the COVID-19 pandemic. We proposed a chain mediation model in which job burnout and affective commitment play mediating roles in this process. Using questionnaire data from 632 Chinese subway employees during February 2020, structural equation modeling analyses were performed. The analyses showed that work-family conflict had a significant negative impact on subway employee safety performan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…When work–family conflicts occur, miners must spend significant time and energy adjusting their emotions and states, making it difficult for them to focus entirely on their work [ 50 ]. Zhang et al [ 51 ] found that work–family conflict had a significantly negative effect on the job performance of subway employees during the COVID-19 pandemic. Bojan showed the indirect effect of work–family conflict with psychological safety as an intermediate variable in employees job performance [ 52 ].…”
Section: Theoretical Background and Hypothesis Developmentmentioning
confidence: 99%
“…When work–family conflicts occur, miners must spend significant time and energy adjusting their emotions and states, making it difficult for them to focus entirely on their work [ 50 ]. Zhang et al [ 51 ] found that work–family conflict had a significantly negative effect on the job performance of subway employees during the COVID-19 pandemic. Bojan showed the indirect effect of work–family conflict with psychological safety as an intermediate variable in employees job performance [ 52 ].…”
Section: Theoretical Background and Hypothesis Developmentmentioning
confidence: 99%
“…Distance learning and working have led to changes in health behaviors [ 10 , 11 ]. Furthermore, people need to face organizational adaptation [ 12 ] and concerns for self-health [ 13 ] when fighting against diseases. These changes indicate that emerging diseases systematically impact human society and require attention from all facets of society.…”
mentioning
confidence: 99%